2005
DOI: 10.1007/s00467-005-1851-7
|View full text |Cite
|
Sign up to set email alerts
|

Neonates with extra-renal pelvis: the first 2 years

Abstract: Extra-renal pelvis (ERpel) is a common ultrasonographic finding among neonates who have undergone recurrent ultrasound examinations for a better definition of prenatal renal pelvic dilatation. This study tries to determine whether or not ERpel has important prognostic implications. Seventy-nine neonates (17 female) were examined. All had a diagnosis of prenatal renal pelvis dilatation, which was shown by postnatal ultrasound to be ERpel. Sixty ERpel neonates were examined 1.5 months to 2.5 months after the ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…The UTI rate in our study group was higher than expected in the normal population: 12.7% in girls vs 7% expected and 6.2% in boys vs 2% expected [22]. Other authors have also noted an increased UTI rate in children with renal dilatation, especially those with calyceal dilatation [1,23,24], but Dremsek et al [2] found the reverse. All five of the children developing severe renal abnormality had calyceal fullness at their 1-week or 6-week sonogram, and one had ureteric dilatation and fluctuation of the renal pelvis also.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The UTI rate in our study group was higher than expected in the normal population: 12.7% in girls vs 7% expected and 6.2% in boys vs 2% expected [22]. Other authors have also noted an increased UTI rate in children with renal dilatation, especially those with calyceal dilatation [1,23,24], but Dremsek et al [2] found the reverse. All five of the children developing severe renal abnormality had calyceal fullness at their 1-week or 6-week sonogram, and one had ureteric dilatation and fluctuation of the renal pelvis also.…”
Section: Discussioncontrasting
confidence: 59%
“…From 1-4% of all children are investigated in the postnatal period because of foetal renal pelvic dilatation [1][2][3]. The proportion undergoing further investigation depends on the foetal renal pelvic cut-off level selected for further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, renal Doppler sonogram is not a practical method in uncooperative young children. Katzir et al reported that neonates with extra renal pelvis had an increased UTI incidence unrelated to VUR within the first two years 9) . In this study, extra renal pelvis was included as a parameter of hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated dilation of the extrarenal pelvis is usually considered a benign finding (25). One study showed that while infants extra-renal pelvis dilation have slightly higher rates of UTI, it resolves in 98% of patients on followup (26). Furthermore, dilation of the intra-renal pelvis has by far as more significant prognostic values, as highlighted by the adoption of anterio-posterior renal pelvis diameter by the UTD classification (27).…”
Section: Diagnosis and Initial Evaluationmentioning
confidence: 99%